2016
DOI: 10.18239/ocnos_2016.15.1.866
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la implicación familiar en estudiantes con riesgo de dificultad lectora

Abstract: El entorno familiar influye notablemente en numerosos aspectos educativos. Una parte de la población escolar que requiere atención especial son los alumnos que presentan Dificultades de Aprendizaje en la Lectura (DAL). A partir del programa de lectura en familia “¿Me lees un cuento, por favor?”, se busca comprobar si la implicación de los padres en la lectura de sus hijos mejora su aprendizaje. Para ello se realizó un diseño cuasi-experimental pretest-postest con grupo de control. Los participantes fueron 206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
4
1
0
1
Order By: Relevance
“…With respect to the decoding variable, an improvement was found in the scores for both word reading and reading without meaning. This confirms the positive effect of an HLE (A) program on reading recognition, in accordance with the data found by Mora-Figueroa et al (2016) and Niklas and Schneider (2014) [ 14 , 34 ]. In their respective studies, these researchers observed an improvement in reading decoding (identification of letters, and recognition of words and pseudowords) following the application of HLE (A) programs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With respect to the decoding variable, an improvement was found in the scores for both word reading and reading without meaning. This confirms the positive effect of an HLE (A) program on reading recognition, in accordance with the data found by Mora-Figueroa et al (2016) and Niklas and Schneider (2014) [ 14 , 34 ]. In their respective studies, these researchers observed an improvement in reading decoding (identification of letters, and recognition of words and pseudowords) following the application of HLE (A) programs.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our expectations, it can be stated, following analysis of the data, that between the first and last evaluation—that is, after two academic years—improvements were found in all variables, except in verbal fluency, for which scores did not increase, but were positioned around the population mean. Thus, in line with the results obtained by other authors, we were able to demonstrate the efficacy of the HLE (A) program for the improvement of psycholinguistic variables associated with reading [ 4 , 14 , 34 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consideramos que toda intervención ha de ser global y debe incluir el entorno familiar para que este no se transforme en un espacio de malestar emocional y desarrollo de problemas de convivencia (Musitu, Estévez, Jiménez y Vega, 2011). El compromiso familiar en el proceso educativo de los hijos en relación con el rendimiento ha sido confirmado en numerosos estudios (Fajardo, Maestre, Felipe, León y Polo, 2017;Mora-Figueroa, Galán y López-Jurado, 2016). La familia también puede actuar como un espacio de entrenamiento en habilidades sociales, proporcionando experiencias positivas para establecer relaciones sociales adecuadas.…”
Section: Discussionunclassified